Adalbert Stifter's Poetics of Clouds and Nineteenth-century Meteorology. (1st October 2016) - Maurer, Kathrin
Abstract : This article examines the representation of clouds in Adalbert Stifter's (1805–68) literary writing. His ubiquitous representations of clouds signify the poetic challenges to represent empirical reality of natural phenomena (such as weather phenomena) within the literary medium. The article connects his representation of clouds with scholarly discourses of meteorology during the nineteenth century and offers as context observations by the meteorologist Andreas von Baumgartner (1793–1865). Baumgartner worked as a Professor of Natural Sciences at the University of Vienna and was a friend of Stifter's. Taking Baumgartner's epistemological ambiguities about the weather as a point of departure, the article demonstrates how Stifter's novella Kalkstein (1853) not only displays similar insecurities, but also how the text makes use of them to reflect the possibilities of poetic representation within the mode of literary realism.